2022
DOI: 10.1002/advs.202201802
|View full text |Cite
|
Sign up to set email alerts
|

Aliovalent Dilute Doping and Nano‐Moiré Fringe Advance the Structural Stability and Thermoelectric Performance in β‐Zn4Sb3

Abstract: Thermoelectric (TE) generators have come a long way since the first commercial apparatus launched in the 1950s. Since then, the β‐Zn4Sb3 has manifested its potential as a cost‐effective and environmentally friendly TE generator compared with the tellurium‐bearing TE materials. Although the β‐Zn4Sb3 features an intrinsically low thermal conductivity κ, it suffers from a long‐lasting structural instability issue arising from the highly mobile zinc ions. Herein, the dilute Ga dopant gives rise to the aliovalent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Through the introduction of Na and Ga, the carrier optimization is realized and results in a higher PF and ZT value in the samples with x = 0.08 and 0.12. The maximal ZT value reached 1.73 at 690 K, which is 22% higher than that of the Zn 4.1 Sb 3 (NaCl) 7 sample (1.42 at 690 K) and also better than the value reported earlier by Jen (ZT max = 1.4 at 623 K) . This work suggests that dilute Ga doping is an effective way of optimizing thermoelectric properties.…”
Section: Results and Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Through the introduction of Na and Ga, the carrier optimization is realized and results in a higher PF and ZT value in the samples with x = 0.08 and 0.12. The maximal ZT value reached 1.73 at 690 K, which is 22% higher than that of the Zn 4.1 Sb 3 (NaCl) 7 sample (1.42 at 690 K) and also better than the value reported earlier by Jen (ZT max = 1.4 at 623 K) . This work suggests that dilute Ga doping is an effective way of optimizing thermoelectric properties.…”
Section: Results and Discussionmentioning
confidence: 39%
“…The maximal ZT value reached 1.73 at 690 K, which is 22% higher than that of the Zn 4.1 Sb 3 (NaCl) 7 sample (1.42 at 690 K) and also better than the value reported earlier by Jen (ZT max = 1.4 at 623 K). 52 This work suggests that dilute Ga doping is an effective way of optimizing thermoelectric properties. Since the average ZT (ZT ave ) values are important for thermoelectric generators, the ZT ave of all samples for different Ga doping amounts can be calculated according to the following formula…”
mentioning
confidence: 93%
“…[22][23][24][25]34 It is reported that V Mg does not exist in the single-crystal region, whereas V Mg aggregates to form the dark gray regions symbolized by a striped pattern, namely, a Moiré pattern. 44,45 To examine the light gray and dark gray regions in the x = 0.020 SC, the R2 region in Fig. 2b 2b; the dark gray region was the Moiré pattern.…”
Section: Crystal Structurementioning
confidence: 99%
“…By incorporating IIIA dopants into Zn 4 Sb 3 , we have demonstrated enhanced structural stability alongside improved TE performance. 14,15 By synergistically combining cationic interstitial doping and phase diagram engineering, we have successfully developed Al−Zn 4 Sb 3 , which exhibits an improved power factor PF = S 2 σ and a 20% increase in peak zT compared to pristine Zn 4 Sb 3 . While the enhancement in the peak zT may appear subtle, the most striking outcome is the doubling of η in Al−Zn single-leg device, particularly at a temperature difference (ΔT) of 300 K. To the best of our knowledge, this research marks a significant milestone by successfully assembling the first singleleg devices using fully dense Zn 4 Sb 3 .…”
Section: ■ Introductionmentioning
confidence: 99%